Effectiveness of Sweet Orange Peel Pectin Nanoparticles as Edible Coating on The Quality of Pondoh Salak Fruit (Salacca edulis Reinw.) - Kania, Dewi; Ananda, Sinta Margareta; Rahmawati, Puspita Sari Dewi; Sukorini, Henik; Roeswitawati, Dyah; Santoso, Untung; Indratmi, Dian (Agrikan Jurnal Agribisnis Perikanan, 2024)
Harvest damage to snakefruit (Salacca edulis Reinw.) easily occurs, this is very different from other horticultural plants. Damage to snakefruit occurs due to attack by white fungus which causes the fruit to become rotten and watery. The aim of this research is to find an edible coating made from sweet orange peel pectin nanoparticles that is able to maintain the quality of snakefruit during storage. This research was carried out at the Agrotechnology Laboratory of the University of Muhammadiyah Malang from June to September 2023. The results of this research are the use of pectin in edible coatings with various types of approval as follows. P0 represents control; P1 represents 1% pectin; P2 represents 2% pectin; P3 represents 3% pectin; and P4 represents 4% pectin. The parameters observed were weight loss, percentage of disease incidence, hardness, and sensory tests. The results obtained from these four parameters show that in sample P4 with a sweet orange peel pectin concentration of 4%, the shelf life of snakefruit can be extended to 15 days with better quality compared to samples P0, P1, P2, P3, P4. Edible coating made naturally from orange peel pectin has a beneficial effect on snakefruit because it can extend the shelf life of snakefruit by up to 15 days. In fact, the appearance of snakefruit increases its brightness from the beginning of the fruit's shelf life. This is the best choice for further coating development.